2013
DOI: 10.1016/j.yexcr.2013.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C regulates FLT1 abundance and stimulates its cleavage in vascular endothelial cells with the release of a soluble PlGF/VEGF antagonist

Abstract: FLT1 and its soluble form (sFLT1) arise as alternate transcripts from the same gene and sFLT1 can antagonize the effect of vascular endothelial growth factor (VEGF) on its cognate receptors. We investigated the effect of VEGF and protein kinase C (PKC) activation on sFLT1 abundance. We demonstrated that VEGF stimulates sFLT1 and FLT1 mRNA and protein levels in vascular endothelial cells via VEGFR2 and PKC. Using an FLT1 expression vector with N and C-terminal epitope tags, we show that PKC activation increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 29 publications
3
31
0
Order By: Relevance
“…The extracellular domain can bind VEGF and PlGF and is very similar to the transcriptionally derived sFlt1 [15]. We also demonstrated that PMA stimulated an increase in the abundance of Flt1 in HUVEC which was completely inhibited by GF109203X.…”
Section: Discussionmentioning
confidence: 56%
“…The extracellular domain can bind VEGF and PlGF and is very similar to the transcriptionally derived sFlt1 [15]. We also demonstrated that PMA stimulated an increase in the abundance of Flt1 in HUVEC which was completely inhibited by GF109203X.…”
Section: Discussionmentioning
confidence: 56%
“…We have reported that s FLT1 was expressed, at least at the mRNA level, in CTBs, at about 1000 fold more than FLT1 (4). We have also previously reported that, in addition to its transcriptional origin, sFLT1 can be derived by post-translational cleavage of FLT1(6). We were not able to detect FLT1 by immunoblotting in CTBs, presumably because of its low abundance (Figure 1A).…”
Section: Resultsmentioning
confidence: 90%
“…C-terminal GFP-tagged open reading frame (ORF) clone of full length human VEGFR2 was purchased from OriGene (Rockville, MD). Recombinant adenovirus expressing FLT, sFLT1-i13, sFLT1-e15a and control virus were generated by the vector Core Facility at the University of Iowa and has been previously described (4, 6). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations